Hesitancy to COVID-19 Vaccines among University Students in Lebanon. (March 2022) - Hamdan, M. Bou; Singh, S.; Polavarapu, M.; Jordan, T.; Melhem, N.
Abstract : Purpose: The aim of the study is to assess the readiness and behavioral intentions of students enrolled at the American University of Beirut (AUB), Lebanon to obtain the COVID-19 vaccine. To our knowledge, this is the first study to assess vaccine hesitancy among university students in Lebanon. Methods & Materials: We conducted an online survey between May 11 and June 18, 2021 administered to a total of 3805 undergraduate and graduate students. We used three models as the theoretical framework of the study. These include the Integrated Behavioral Model (IBM) (to assess attitude, perception and behavioral intentions), Precaution Adoption Process Model (PAPM) (to assess readiness to adopt a preventive health behavior), and the Extended Parallel Processing Model (EPPM) (to assess cognition and emotional reactions). Chi square and logistic regression were performed using STATA. Results: The study included 800 participants (21.02%) from all faculties (n=7) at AUB. The mean age was 21 years with the majority being undergraduate students (75%). The vaccine acceptance group represented 87.01% of the study participants while the hesitant and refusal groups accounted for 10.21%, and 2.77%, respectively. Our results showed that hesitancy was significantly associated with nationality, residency status and university rank (p value< 0.05). Moreover, there was a significant association between hesitancy and agreement/disagreement to the conspiracy type of thinking questions. Interestingly, the majority of the hesitant group agreed that the mainstream media is creating unnecessary fear towards COVID-19 (54.43%) and that millions more people per year die from flu than from COVID-19 (40.51%). Students reporting that pharmaceutical companies adequately tested the safety of the vaccine (OR=0.52; 95% CI=0.19-1.43; p value=0.21) and those who consider the vaccine in agreement with their personal views (OR= 0.11, 95% CI= 0.02-0.51, p value= 0.004) were less likely to be hesitant. Interestingly, history of COVID-19 infection didn't affect the participants' willingness to get vaccinated. Conclusion: Our results showed a low hesitancy rate among students enrolled at AUB. The factors associated with hesitancy can be used as a core content to organize social campaigns for spreading awareness and increasing the acceptance rate of COVID-19 vaccination.